The Construction of Strategic Narrative in the Saudi-Iranian Regional Rivalry: The Case of the Yemeni Civil War - Akdoğan, İsmail; Küpeli, Mustafa Şeyhmus; Gürler, Recep Tayyip (İlmi Etüdler Derneği, 2022)
This study discusses strategic narratives of Saudi Arabia and Iran through the example of the Yemeni Civil War (2011-2021). During their regional power struggle, the two countries construct their narratives against each other by means of the media. The strategic narratives of Saudi Arabia and Iran are examined at three levels: issue, identity and system narratives. The research has intended to determine how the media of the two countries define the Yemeni Civil War, the identity references they have made to each other and the type of regional order they have envisioned. An issue-based news survey was conducted a ten-year period by selecting three international media outlets of Iran and Saudi Arabia. The news texts were analyzed by applying the qualitative content analysis technique. . It was observed that by using the strategic narrative as a tool, the two regional rival powers made a great effort to present their attitudes and behavior as legitimate, and the other side as illegitimate in the presence of international public opinion.
Keywords: Political Science; Siyaset Bilimi [EN] International Relations; Uluslararası İlişkiler